Harvesting and handling effects on postharvest decay - Michailides, Themis J.; Manganaris, George A. (My University, 2009)
Purpose of review: The aims of this review are: (1) to highlight the most significant results over the last few years in harvesting methods and pre- and postharvest handling of horticultural products; and (2) to provide insights in terms of technological aspects, with special reference to the control of postharvest decay. New system approaches that should be considered as components of an integrated decay control strategy and overall good agricultural practices are also described. Main findings: Harvest and handling practices have major effects on postharvest decay. Mechanical harvesting systems and time of harvest have a prominent effect on postharvest decay and mycotoxin contamination. Fruit maturity at harvest, which directly affects bruising, is a major factor affecting infection by postharvest pathogens. Harvest of fruits from the ground and contact of harvest containers with soil contaminate fruits with postharvest propagules and result in increased decay. Climatic conditions affect sources of contamination and infection of fruits: under dry, hot subtropical climates latent and quiescent infections preharvest play a significant role while under warm, humid tropical climates contamination of fruit wounds during harvest can be of great importance, affecting levels of postharvest decay. Packing directly in the field reduces production costs but increases chances for postharvest decay. Electronic noses have been constructed that can "smell" and separate decayed fruits in packinghouses and predict mycotoxin contamination. Regression models have been developed to detect the impact of mechanical damage on postharvest decay. In addition, new packaging systems have been created to minimise mechanical injuries and decrease susceptibility to decay and bruising. Postharvest treatments, such as application of reduced-risk fungicide, biological agents and natural products, heat treatment and edible coating formulations, alone or in combination, can be successfully applied in a range of commodities in order to prevent decay. Directions for future research: The mode of action of antagonistic yeast in postharvest fruit disease control may be an important tool in postharvest biocontrol strategies, thus providing important guidance for their future application. In addition, mixtures of low-risk fungicides with biological agents should be carried out to identify the best postharvest treatments with the lowest environmental impact and the greatest consumer safety. Comparative studies for a range of fleshy products harvested from organic, integrated and conventional production systems should be also carried out
Keywords: Edible coatings; Fungal pathogens; Heat treatment; Maturity stage; Biological agents; Mechanical harvest